2016
DOI: 10.21149/spm.v58i2.7784
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in the Mexican Social Security Institute, 1989-2013

Abstract: Objective. To analyze cancer mortality in affiliates of the Mexican Social Security Institute (Instituto Mexicano del Seguro Social -IMSS) and time trends in the risk of death due to cancer from 1989 to 2013. Materials and methods. A descriptive analysis of cancer mortality trends in beneficiaries of the IMSS was performed. Age-and sex-adjusted mortality rates were obtained using direct standardization with the WHO population. Changes in the risk of death due to cancer over time were evaluated using Poisson re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…In northeast Mexico, ALL is the principal cause of death by malignant cancer in children and adolescents between 0 and 19 years, accounting for 48.5% of all cases [7]. We documented 437 patients with ALL in the study period with an M:F ratio of 1.1:1, slightly lower than 1.3:1 reported in the US [10] but the same as that found in the UK, 1.1:1 [11].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In northeast Mexico, ALL is the principal cause of death by malignant cancer in children and adolescents between 0 and 19 years, accounting for 48.5% of all cases [7]. We documented 437 patients with ALL in the study period with an M:F ratio of 1.1:1, slightly lower than 1.3:1 reported in the US [10] but the same as that found in the UK, 1.1:1 [11].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…Leukemias were the seventh cause of death due to malignancy among individuals aged 20 years and older, accounting for 1259 deaths, 4.2% of total cancer deaths in Mexico during 2013 [7]. The frequency, age and sex of the patients with acute and chronic leukemias at two large centers in Mexico City were recently reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…While previous analyses 5,[9][10][11] have examined time trends, data on the burden of colorectal cancer according to state and healthcare insurance status in the Mexican population is scarce. In effort to understand the at-risk populations who are most likely to benefit from CRC screening interventions, we aimed to describe the burden of CRC in Mexico, according to state of residence and insurance status, and changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that breast cancer is one of the main causes of death in women around the world [1]. In Mexico, breast cancer is the main reason of deaths in adult women in ages among 30 and 54 years [2] [3]. It is also one of the currently most common cancers in Mexico, with high risk.…”
Section: Introductionmentioning
confidence: 99%